2010
DOI: 10.1128/aem.00620-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Brucella Strains Originating from Wild Native Rodent Species in North Queensland, Australia

Abstract: We report on the characterization of a group of seven novel Brucella strains isolated in 1964 from three native rodent species in North Queensland, Australia, during a survey of wild animals. The strains were initially reported to be Brucella suis biovar 3 on the basis of microbiological test results. Our results indicated that the rodent strains had microbiological traits distinct from those of B. suis biovar 3 and all other Brucella spp. To reinvestigate these rodent strains, we sequenced the 16S rRNA, recA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 43 publications
1
85
0
1
Order By: Relevance
“…The use of multilocus sequence analysis (MLSA) opens the way to detailed characterization of the global population structure of Brucella (Whatmore et al, 2007). These analyses confirmed the status of the classical species as distinct genetic entities, began to index intra-species diversity and relate this to historical biovar designations, and provided a framework for the placement of atypical or emerging Brucella isolates Schlabritz-Loutsevitch et al, 2009;Tiller et al, 2010). Further, these analyses and the availability of more robust phylogenetic histories, allowed the identification of canonical single nucleotide polymorphisms (SNPs) that could be exploited as the basis of rapid diagnostic tests.…”
Section: Molecular Detection and Identificationmentioning
confidence: 84%
See 1 more Smart Citation
“…The use of multilocus sequence analysis (MLSA) opens the way to detailed characterization of the global population structure of Brucella (Whatmore et al, 2007). These analyses confirmed the status of the classical species as distinct genetic entities, began to index intra-species diversity and relate this to historical biovar designations, and provided a framework for the placement of atypical or emerging Brucella isolates Schlabritz-Loutsevitch et al, 2009;Tiller et al, 2010). Further, these analyses and the availability of more robust phylogenetic histories, allowed the identification of canonical single nucleotide polymorphisms (SNPs) that could be exploited as the basis of rapid diagnostic tests.…”
Section: Molecular Detection and Identificationmentioning
confidence: 84%
“…To date the genus Brucella consists thus of 10 species. Prospective Brucella species have also been isolated from three native rat species in Australia, but not yet been included in the genus (Tiller et al, 2010) as well as in association with two cases of stillbirth in non-human primates (Schlabritz-Loutsevitch et al, 2009). The preferential hosts and the pathogenicity for humans of the 10 recognized Brucella species are depicted in Table 1.…”
Section: Taxonomy and Taxonomical Controversiesmentioning
confidence: 99%
“…Within the last few years, potential novel species of Brucella have been isolated from various sources, including rodents (Tiller et al, 2010), different frog species (Eisenberg et al, 2012;Fischer et al, 2012;Whatmore et al, 2015), red foxes (Hofer et al, 2012) and a blue dotted ray (T. Eisenberg and H. C. Scholz, unpublished data), and are awaiting final genus affiliation. Although genome similarities of these potential novel species of Brucella are still above 90 % compared with classical species (Wattam et al, 2009;this study), the majority of these novel candidates carries genetic information not found in classical species but similar to genetic information found in other soil-living bacteria, such as Ochrobactrum, Paracoccus denitrificans, Agrobacterium and Sinorhizobium.…”
mentioning
confidence: 99%
“…Zoonotic potential is classified as pathogenicity and virulence in human hosts. Original citation indicates the original publication where the species was characterized.SpeciesNatural hostZoonotic Potential [8]Original Citation B. melitensis Sheep, goats, and camelsYes – High[5] B. abortus Cattle, elk, and bisonYes – High[6] B. suis Pigs, hare, reindeer/caribouYes – High[122] B. canis Dogs (domestic and wild)Yes – Moderate[123] B. ovis SheepNo reported infections[124] B. neotomae Desert wood ratsNo reported infections[125] B. ceti CetaceansYes – Low[126] B. pinnipedialis PinnipedsYes – Low B. microti Red foxes and common volesNo reported infections[127] B. inopinata UnknownYes – High[2,128] B. papionis Non-Human PrimatesNo reported infections[129,130] B. vulpis Red foxNo reported infections[131,132] Brucella NFXXXX Australian ratNo reported infections[133,134]…”
Section: Introductionmentioning
confidence: 99%